1999
DOI: 10.1523/jneurosci.19-18-08083.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Interactions Improve Cortical Population Coding of Movement Direction

Abstract: Interactions among groups of neurons in primary motor cortex (MI) may convey information about motor behavior. We investigated the information carried by interactions in MI of macaque monkeys using a novel multielectrode array to record simultaneously from 12-16 neurons during an arm-reaching task. Pairs of simultaneously recorded cells revealed significant correlations in their trial-to-trial firing rate variation when estimated over broad (600 msec) time intervals. This covariation was only weakly related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
174
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(193 citation statements)
references
References 54 publications
17
174
2
Order By: Relevance
“…Variations of noise correlations with respect to speed of moving targets and movement direction have been reported in pairs of MT and motor-cortical neurons, respectively (42,43). Our study provides a theoretical framework to test hypotheses on how a particular underlying connectivity and dynamical properties structure the fluctuations in neural networks.…”
Section: Discussionmentioning
confidence: 66%
“…Variations of noise correlations with respect to speed of moving targets and movement direction have been reported in pairs of MT and motor-cortical neurons, respectively (42,43). Our study provides a theoretical framework to test hypotheses on how a particular underlying connectivity and dynamical properties structure the fluctuations in neural networks.…”
Section: Discussionmentioning
confidence: 66%
“…Churchland et al (2006) determined that ϳ50% of the variance in performance was already present in these cortical neural signals rather than arising from the "motor noise" that has been attributed to discrete recruitment of size-ordered motor units (Jones et al, 2002). It is also likely that the cortical variability is itself correlated among multiple units (Maynard et al, 1999). Churchland et al (2006) interpreted this variability as noise, but it may be indicative of purposeful exploration of the complex solution space afforded by an SLR to which these neurons project.…”
Section: The General Utility Of Regulatorsmentioning
confidence: 99%
“…These studies have led to the view that cortical neurons act as independent processors of information (Gochin et al, 1994;Rolls et al, 1997Rolls et al, , 2004Reich et al, 2001;Purushothaman and Bradley, 2005). Although correlations between neurons may be important factors for neural coding (Zohary et al, 1994;Vaadia et al, 1995;Dan et al, 1998;Abbott and Dayan, 1999;Bair et al, 2001;Nirenberg and Latham, 2003;Averbeck and Lee, 2004;Johnson, 2004), few studies have demonstrated that considering neuronal interactions increases predictive information over that contained in individual neurons (Riehle et al, 1997;Hatsopoulos et al, 1998;Gat and Tishby, 1998;Maynard et al, 1999;Averbeck et al, 2003;Samonds et al, 2004). Gawne and Richmond (1993) and, more recently, Schneidman et al (2003) have proposed a theoretical framework for interpreting neuronal ensemble activity in which information encoded by an ensemble of neurons is compared with the sum of information encoded by the component neurons.…”
Section: Introductionmentioning
confidence: 99%